From Positivism to Pragmatism A Systematic Literature Review of Philosophical Paradigms in Management Science - Daniel, Pance; Budiarti, Isniar; Rahayu, Siti Kurnia; Sulistyo, Dedo (CV. ULIL ALBAB CORP, 2026)
This study examines the philosophical foundations of management science through a systematic literature review of 25 journal articles published between 2015 and 2025. The background of this research is the growing complexity of organizational challenges and the need for clearer research paradigms in management studies. Many management studies focus on methods and results, but often do not clearly explain the philosophical assumptions behind them. Therefore, this study aims to identify the dominant research paradigms in management, analyze how these paradigms influence research methods, and understand their contribution to theory and practice. Using a qualitative systematic review approach, the selected articles were analyzed based on ontology, epistemology, methodology, and axiology. The results show that positivism and post-positivism still dominate, especially in strategic management, finance, and risk management research. However, interpretivism, critical realism, critical theory, and pragmatism are increasingly used in studies related to leadership, sustainability, governance, and innovation. The findings indicate a shift toward methodological pluralism and a stronger awareness of ethical and contextual issues in management research. This study concludes that understanding philosophical foundations is important to ensure theoretical clarity, methodological consistency, and practical relevance in management science.